The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0100-29452012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de danos causados por Anastrepha fraterculus (Wiedemann) (Diptera, Tephritidae) e desenvolvimento larval em frutos de duas cultivares de quivizeiro (Actinidia spp.)

Abstract: RESUMO -Os danos causados por A. fraterculus em três estágios de maturação de frutos de quivizeiro foram avaliados em pomar comercial, e, em laboratório, o desenvolvimento larval da espécie foi estudado, nas cultivares MG06 e Bruno. Frutos das duas cultivares foram infestados com A. fraterculus, em pomar comercial localizado em Farroupilha-RS, no início (30% do tamanho final), metade (90% do tamanho final) e final (ponto de colheita) do ciclo de desenvolvimento, e, em laboratório, desde o início da frutificaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…While numerous studies have investigated how fruit variation influences tephritid offspring performance, such studies focus predominantly on evaluating female choice (oviposition preference and the number of laid eggs) and then score the number of F1 pupae or adults emerging (Bino et al, 2004;Fernandes-da-Silva & Zucoloto, 1993;Jang & Light, 1991;Joy Burrack & Zalom, 2008;Lorscheiter, Redaelli, Botton, & Pimentel, 2012). In such studies, the "within fruit" component of the life cycle (i.e.…”
mentioning
confidence: 99%
“…While numerous studies have investigated how fruit variation influences tephritid offspring performance, such studies focus predominantly on evaluating female choice (oviposition preference and the number of laid eggs) and then score the number of F1 pupae or adults emerging (Bino et al, 2004;Fernandes-da-Silva & Zucoloto, 1993;Jang & Light, 1991;Joy Burrack & Zalom, 2008;Lorscheiter, Redaelli, Botton, & Pimentel, 2012). In such studies, the "within fruit" component of the life cycle (i.e.…”
mentioning
confidence: 99%
“…A study on pear fruits of the Packhams and Williams genotypes showed that the complete development of A. fraterculus occurred only in fruits which were 54.9 and 63.5 mm in diameter, respectively, and which had higher soluble solids content (NUNES et al, 2015). The increase in soluble solids content in kiwi fruits was also indicated as an important factor associated with the development of A. fraterculus under laboratory conditions (LORSCHEITER et al, 2012). Means followed by the same letters in the column do not differ from each other by Duncan's test at 5% probability.…”
Section: Resultsmentioning
confidence: 85%
“…mature. In mature fruits, bark texture and pulp consistency (Nunes et al, 2015b), sugar contents (Lorscheiter, Redaelli, Botton, & Pimentel, 2012) and brix degree (Rattanapun, Amornsak, & Clarke, 2009) are predominant factors for fruit fly oviposition behavior. According to Rattanapun et al (2009), mature fruits with higher sugar content are more suitable for larval development, as they ensure a higher survival rate and a shorter development period.…”
Section: Introductionmentioning
confidence: 99%